Photoredox-Enabled Decarboxylative Synthesis of Unnatural α-Amino Acids - Shatskiy, Andrey; Kärkäs, Markus D. (Synlett, 2021)
Recently, development of general synthetic routes to unnatural α-amino acids has gained significant momentum, driven by the high demand for such building blocks in fundamental research within molecular and structural biology, as well as for development of new pharmaceuticals. Herein, we highlight the recent progress in employing photoredox-mediated synthetic methods for accessing unnatural α-amino acids with a focus on various decarboxylative radical-based strategies.
Keywords: amino acids; decarboxylation; photoredox catalysis; radicals